PENGARUH KARAKTERISTIK INDIVIDU, KOMPETENSI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. VEGAS VIVA VENTURY BALI - Ni Gusti Ayu Ade Dwi Yosiana Sari; I Nengah Suardhika; I Gede Rihayana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
This research was conducted at PT. Vegas Viva Ventury Bali, this study aims to determine the effect of Individual Characteristics, Competence and Communication on Employee Performance. The population in this study were all employees of PT. Vegas Viva Ventury Bali. The sample used in this study was 45 respondents using simple random sampling method. The method used in this study is Multiple Linear Regression Analysis. The results showed that individual characteristics and communication had a positive and significant effect on the performance of employees at PT. Vegas Viva Ventury Bali while the charge has a negative and significant effect on the performance of employees of PT. Vegas Viva Ventury Bali.